Halide-free synthesis of Au nanoplates and monitoring the shape evolution process through a marker experiment. Issue 27 (24th June 2016) - Chen, Lei; Hu, Huicheng; Liu, Qipeng; Ji, Fei; Chen, Suli; Xu, Yong; Zhang, Qiao
Abstract : We demonstrate that uniform Au nanoplates capped with a nontoxic ligand have been prepared through a seeded growth method using Au/Ag nanorings as the template. Abstract : We demonstrate that uniform Au nanoplates capped with a nontoxic ligand have been prepared through a seeded growth method using Au/Ag nanorings as the template. A mechanistic study reveals that the growth process experienced both "back-filling" and "out-extending" processes. This research sheds some light on both the synthesis and the potential applications of gold nanoplates.